THE ROLE OF BRAND AMBASSADOR AND BRAND IMAGE ON CONSUMER PURCHASE DECISIONS AT TOKOPEDIA - Andhalia Liza Marie; Tri Djoko Sulistiyo; Rizkita Nurauwel (Universitas Islam Lamongan, 2023)
The research objective was to determine the influence of brand ambassadors and brand image on consumer purchasing decisions. The method used in this research is a quantitative descriptive method. In determining the number of samples using non-probability sampling techniques with sampling techniques using purposive sampling. 115 respondents as research objects as Tokopedia consumers and BTS fans. Data processing uses the SPSS version 26 program to carry out validity tests, reliability tests, descriptive tests, coefficient of determination tests, multiple linear analysis tests. Research data collection was carried out by dividing questionnaires consisting of 23 servers using a Likert scale with five scores online using Google Form. The results of this study partially show that brand ambassadors and brand image have a significant effect on consumer purchasing decisions at Tokopedia.